2008
DOI: 10.1093/ndt/gfm807
|View full text |Cite
|
Sign up to set email alerts
|

Effects of statins on renal sodium and water handling: Acute and short-term effects of atorvastatin on renal haemodynamics, tubular function, vasoactive hormones, blood pressure and pulse rate in healthy, normocholesterolemic humans

Abstract: An acute dose of AS decreased FE(Na) and DBP in healthy humans. The reduction in fractional urinary sodium excretion was very modest and transitory, and most likely secondary to the fall in diastolic blood pressure (DBP). However, renal haemodynamics, tubular function, vasoactive hormones and blood pressure were unchanged during short-term statin treatment in healthy man.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
17
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 20 publications
3
17
2
Order By: Relevance
“…The pleiotropic effects of statins might thus include changes in renal function or vasoactive hormones. In a recent study, we found that atorvastatin had no acute or shortterm effects on renal hemodynamics in healthy men, but our results suggested that atorvastatin may influence renal handling of sodium [9]. No information is available about the effect of changes in dietary sodium intake on GFR and BP in healthy subjects during statin treatment.…”
Section: Introductioncontrasting
confidence: 64%
See 3 more Smart Citations
“…The pleiotropic effects of statins might thus include changes in renal function or vasoactive hormones. In a recent study, we found that atorvastatin had no acute or shortterm effects on renal hemodynamics in healthy men, but our results suggested that atorvastatin may influence renal handling of sodium [9]. No information is available about the effect of changes in dietary sodium intake on GFR and BP in healthy subjects during statin treatment.…”
Section: Introductioncontrasting
confidence: 64%
“…However, sodium balance was not controlled in these studies [9,[16][17][18]. Previously, we studied the acute and short-term effects of atorvastatin on GFR and RPF in healthy men and did not demonstrate any effect on renal haemodynamics, but measured a slight decrease in FE Na after treatment with atorvastatin [9]. These results prompted us to examine the effect of changes in dietary sodium intake on GFR and BP in a randomized, placebo-controlled, crossover study in atorvastatin-treated healthy men.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…The doses used in this work are not therefore predictive of those needed in humans to achieve the same result. A recent study examined the possible effect of atorvastatin administration on renal sodium and water handling in healthy volunteers [47]. Besides causing a modest and transitory decrease in fractional excretion of sodium, atorvastatin treatment had no significant effect on renal function.…”
Section: Discussionmentioning
confidence: 99%